Self-Management Intervention for Reducing Epilepsy Burden Among Adult Ugandans with Epilepsy (SMART-U): Randomised Clinical Trial Protocol - Mbalinda, Scovia Nalugo; Kaddumukasa, Mark; Najjuma, Josephine Nambi; Birungi, Doreen R; Kaddumukasa, Martin Ntambi; Levin, Jennifer B; Still, Carolyn Harmon; Burant, Christopher J; Modi, Avani C; Katabira, Elly T; Sajatovic, Martha (Neuropsychiatric Disease and Treatment, 2024)
Background: People of all ages are affected by epilepsy, a prevalent chronic brain illness that is primarily found in underdeveloped nations. It is very necessary to implement epilepsy self-management techniques to support individuals with epilepsy in order to impact outcomes related to epilepsy. The purpose of this 2-site randomised controlled experiment is to investigate this further, based on encouraging preliminary evidence. Methods: A total of 188 adult people with epilepsy (PWE) attending the neurology clinics at Mulago and Mbarara hospitals and consent to participate in the study will be recruited. They will be randomised into intervention versus enhanced treatment control (eTAU) study groups. The intervention group will receive 12-week “intensive” educational sessions and a 12-week remotely accessed telephone followup stage. The controls will continue in their usual care supplemented by written materials on epilepsy in their preferred language and tailored to the reading level of most patients at the clinic. SMART-U consists of 2 main components: a 12-week “intensive” group format stage and a 12-week remotely accessed telephone follow-up stage. SMART-U will be assessed for acceptability, fidelity, and efficacy compared to eTAU. The primary study outcome is the mean change in cumulative past 24-week seizure frequency (24 weeks prior to the study baseline compared to the 24-week follow-up). Seizure frequency will be via self-report with corroboration by family/support system informants whenever possible. Participants will self-report the seizure frequency (numeric count) that they experienced between baseline and 13 weeks and again between 13 and 24 weeks, and the mean change from baseline to 24 weeks in QOL. Discussion: The curriculum-guided Self-Management intervention for Reducing The epilepsy burden among Ugandans (SMART-U) program is anticipated to reduce the epilepsy burden seizure frequency and improve other health outcomes, including depression, functional status and health resource use
Keywords: Self-management; Epilepsy; Targeted management; Intervention